Tahap peningkatan kemahiran insaniah melalui khidmat komuniti pelajar kokurikulum UTM - Tarni, Noraishah (2013)
This study is a survey to identify the improvement of soft skills level among UTM co-curricular students in their community service. Soft skills consist of seven skills of communication skills, critical thinking and problem solving skills, teamwork skills, lifelong learning and information management, entrepreneurial skills, professional ethics and morality, and leadership skills. In addition, this study also examines the relationship between the improvement of soft skill level and the courses of the students as well as examines the differences between community service in the city and in rural areas. This study was conducted a study using survey questionnaire as instrument. The population involved in this study was a group of UTM co-curricular students. The data obtained was analyzed descriptive and inferential by using a “Statistical Package for the Social Sciences Version 16.0” (SPSS 16.0) software. The results showed that the level of soft skills among UTM co-curricular student in community service was as high as 87.4%. The inferential statistics has shown a significant relationship between the improvements of soft skill level and the courses of the students. While no significant differences between community service in the city and in rural areas.